2015
DOI: 10.7314/apjcp.2015.16.15.6783
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 Genotype and Risk of Recurrence in Tamoxifen Treated Breast Cancer Patients

Abstract: Background: Despite consistent pharmacogenetic effects of CYP2D6 on tamoxifen exposure, there is considerable controversy regarding the validity of CYP2D6 as a predictor of tamoxifen outcome. Understanding the current state of evidence in this area and its limitations is important for the care of patients who require endocrine therapy for breast cancer. Materials and Methods: A total of 101 patients with breast cancer who received tamoxifen therapy for at least 3 years, were genotyped for common alleles of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Previous study reported the prevalence of CYP2D6*10 as ~9.0% in Iranian Azerbaijanis (26), but another study of Iranians of different ethnicities reported the prevalence of the allele to be 39.3% (24.3% for homozygous T/T and 15.0% for heterozygous C/T) (25). The frequency of CYP2D6*4 varies across different races, and frequencies of 36.6, 28.6, 28.0, 13.8, 13.8, 7.3 and 0.2% have been reported in Iranians, Malaysian Indians, Turks, Spanish subjects, Brazilians, South-Indians and North Americans, respectively (18,(36)(37)(38)(39)(40)(41). Conversely, the frequency of CYP2D6*4 varies from 0.2 to 3.5% among Japanese, Chinese and Saudi Arabians, which is considered relatively low (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study reported the prevalence of CYP2D6*10 as ~9.0% in Iranian Azerbaijanis (26), but another study of Iranians of different ethnicities reported the prevalence of the allele to be 39.3% (24.3% for homozygous T/T and 15.0% for heterozygous C/T) (25). The frequency of CYP2D6*4 varies across different races, and frequencies of 36.6, 28.6, 28.0, 13.8, 13.8, 7.3 and 0.2% have been reported in Iranians, Malaysian Indians, Turks, Spanish subjects, Brazilians, South-Indians and North Americans, respectively (18,(36)(37)(38)(39)(40)(41). Conversely, the frequency of CYP2D6*4 varies from 0.2 to 3.5% among Japanese, Chinese and Saudi Arabians, which is considered relatively low (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some published studies demonstrate a higher risk of recurrence of the disease and shortening of DFS in patients carrying functionally variant alleles of CYP2D6 (Bonanni et al 2006, Goetz et al 2005, Newman et al 2008, Schroth et al 2007, Trojan et al 2013, Yazdi et al 2015.…”
Section: Vol 64mentioning
confidence: 99%
“…Nedavno je takođe pokazano da u poređenju sa drugim ženama koje imaju rak dojke i primaju tamoksifen, one koje imaju HER2 (engl. human epidermal growth factor receptor 2)/neu pozitivni rak dojke i koje su još i CYP2D6 izrazito brzi metabolizeri tamoksifena usled prisustva više kopija gena za CYP2D6, imaju manju stopu recidiva (27).…”
Section: Tabela I Cyp2d6 Polimorfizmi I Karakteristikeunclassified